Current status of cardiac CT for the detection of myocardial ischemia - Schuhbaeck, A.; Marwan, Mohamed; Cury, R. C.; Achenbach, Stephan (Herz, 2013)
Stress and rest myocardial perfusion imaging using computed tomography (CT) can be accurately and safely performed. CT angiography allows for the anatomic visualization of coronary lesions and the components of atherosclerotic plaque, whereas according to currently available data, CT perfusion imaging improves the diagnostic accuracy for detecting ischemic lesions. However, the radiation exposure and contrast load that are involved cannot be neglected. Owing to the limited number of trials that have been published so far, and the fact that they used a wide variety of image acquisition and stress protocols, a standard acquisition protocol for CT perfusion imaging still needs to be found and evaluated in larger multicenter trials. Therefore, CT perfusion imaging, as opposed to other modalities such as magnetic resonance perfusion, SPECT, or positron emission tomography, cannot yet be regarded as clinical routine, but may be considered in patients with contraindications for other imaging modalities. © 2013 Urban & Vogel.
CRIS-Team Scopus Importer:2023-03-08
Keywords: Cardiac computed tomography; Myocardial ischemia; Myocardial perfusion imaging; Pharmacologic stress; Significant coronary stenoses